Herpes Virus Pseudotumor in a Patient with HIV Immunosuppression. (7th July 2022) - York, Daniel; Patel, Pavan; Saikumar, Smera
Abstract : Background . In rare cases, HSV infections can present as pseudotumors that are often mistaken as malignancies in patients with an uncontrolled HIV infection. Herpes simplex virus type 2 (HSV-2) infection rates range from 60% to 90% in individuals coinfected with HIV. Case Presentation . A 48-year-old patient presented with a large fungating mass near her right inferior vulva with a hardness of surrounding tissues. The mass was 4 cm × 3 cm in size and was excised in the operating room. The pathology was negative for malignancy; however, it showed lymphoplasmacytic proliferation with immunostaining positive for HSV virus. Conclusion . Atypical HSV pseudotumors should be considered in the differential diagnosis for an immunosuppressed patient who presents with a genital mass lesion.